Identifying the features of structural and phase transformations during the processing of oxide waste from the production of high-speed steel - Volokh, Vadym; Poliakov, Anatolii; Rebenko, Victor; Andreev, Andrey; Yamshinskij, Mykhail; Lukianenko, Ivan; Kurlov, Viacheslav; Chaplyhin, Yevhen; Vlasenko, Nataliya; Ivanchenko, Dmytro (Eastern-European Journal of Enterprise Technologies, 2023)
Peculiarities of phase and structural transformations during the carbon-thermal recovery of high-speed steel slag with the production of an alloying additive were investigated. This is necessary to determine the technological indicators that allow reducing the loss of high-value elements during the production and use of the alloying additive. A gradual change in the degree of scale reduction from 32 % to 69 % and 77 % led to an increase in the appearance of the solid solution of alloying elements and carbon in the α-Fe lattice with respect to FeWO4 and Fe3O4. Along with this, Fe3C, FeW3C, WC, VC, V2C, and Cr3C2 were manifested. At the same time, the formation of polyhedral and rounded particles of different chemical composition and the formation of a spongy microstructure was observed. It was determined that the most acceptable degree of recovery is 77 %. At the same time, the degree of reduction of 69 % is also sufficient since due to the residual carbon in the form of carbides, an increased reduction capacity is ensured with additional reduction of the oxide component in the liquid metal during alloying. The spongy microstructure provides relatively fast dissolution compared to standard ferroalloys, which causes a reduction in the total melting time while reducing the resources spent. No phases and compounds characterized by an increased tendency to sublimation were detected in the obtained alloying additive. That is, there is no need to provide additional conditions that prevent the loss of high-value elements during evaporation with the gas phase, which causes an increase in the degree of extraction of alloying elements. The indicators of the obtained alloying additive make it possible to melt alloyed steel in an electric arc furnace with respect to brands whose composition does not have strict restrictions on carbon, while replacing a part of standard ferroalloys.